Pengaruh Kualitas Produk, Online Customer Review dan Online Customer Rating Terhadap Kepuasan Nasabah Dalam Menggunakan Aplikasi M Banking KB Star - Amelya Dwi Fitriani; Riyandi Nur Sumawidjaja; Erna Herlinawati; Dadan Abdul Aziz (Komunitas Dosen Indonesia, 2026)
The rapid transition of the banking sector to digital operations has been accelerated by the development of information technology, particularly mobile banking services. Mobile banking allows customers to easily manage their finances, eliminating the need to visit traditional bank branches. The aim of this study is to examine the impact of product quality, online customer reviews, and online customer ratings on customer satisfaction among users of the KB Star mobile banking app. The study utilized a numerical strategy that incorporates both descriptive and validation techniques. The Lemeshow method was used to select the research sample, which included a total of 100 participants. Data analysis was conducted through validity and reliability tests, classical assumption testing, and multiple linear regression analysis using SPSS 25. The findings indicate that Product Quality has a significant effect on Customer Satisfaction, while Online Customer Reviews and Online Customer Ratings do not show significant partial effects. However, when analysed simultaneously, all three variables significantly influence Customer Satisfaction. These results highlight that application quality, especially system reliability and effectiveness, plays a crucial role in shaping user satisfaction. Therefore, improving digital service quality is essential to enhance customer satisfaction and strengthen user commitment to the KB Star mobile banking application.